Monoassociation with Lactobacillus acidophilus UFV-H2b20 stimulates the immune defense mechanisms of germfree mice - Neumann,E. (1998)
Probiotics are formulations containing live microorganisms or microbial stimulants that have some beneficial influence on the maintenance of a balanced intestinal microbiota and on the resistance to infections. The search for probiotics to be used in prevention or treatment of enteric infections, as an alternative to antibiotic therapy, has gained significant impulse in the last few years. Several studies have demonstrated the beneficial effects of lactic acid bacteria in controlling infection by intestinal pathogens and in boosting the host's nonspecific immune response. Here, we studied the use of Lactobacillus acidophilus UFV-H2b20, a lactic acid bacterium isolated from a human newborn from Viçosa, Minas Gerais, Brazil, as a probiotic. A suspension containing 108 cells of Lactobacillus acidophilus UFV-H2b20 was inoculated into groups of at least five conventional and germfree Swiss mice to determine its capacity to stimulate the host mononuclear phagocytic activity. We demonstrate that this strain can survive the stressing conditions of the intestinal tract in vivo. Moreover, the monoassociation of germfree mice with this strain for seven days improved the host's macrophage phagocytic capacity, as demonstrated by the clearance of a Gram-negative bacterium inoculated intravenously. Monoassociated mice showed an undetectable number of circulating E. coli, while 0.1% of the original inoculum was still present in germfree animals. Mice treated with viable or heat-killed Lactobacillus acidophilus UFV-H2b20 presented similarly improved clearance capacity when compared with germfree controls. In addition, monoassociated mice had twice the amount of Kupffer cells, which are responsible for the clearance of circulating bacteria, compared to germfree controls. These results suggest that the L. acidophilus strain used here stimulates a nonspecific immune response and is a strong candidate to be used as a probiotic.